An antibacterial copper composite more bioactive than metallic silver. Issue 24 (3rd June 2016) - Ben-Knaz Wakshlak, Racheli; Pedahzur, Rami; Menagen, Barak; Avnir, David
Abstract : Entrapment of chlorhexidine within antibacterial copper leads to the formation of a metal composite, whose bactericidal activity exceeds that of silver and that of its individual components. Since the cost of copper is by far lower than that of silver, high volume applications become more accessible. Abstract : Although known for its biocidal activity, copper is still not considered as a viable alternative to silver in many of its biocidal applications, mainly because it is generally considered to be a milder antibacterial metal. As copper is much cheaper than silver (1/100), it is potentially more accessible to the health and hygiene needs of third-world countries, to large volume consumer products, and to large-scale agricultural and water treatment needs. Therefore, enhancing the biocidal efficacy of copper is a sought-after goal. We report a method for achieving this goal: by entrapping molecules of the biocidal agent chlorhexidine (CH) within a metallic copper metal powder, using a new materials methodology, the antibacterial efficacy of copper towards two model nosocomial opportunistic bacteria – the Gram-negative Pseudomonas aeruginosa and the Gram-positive Staphylococcus epidermidis – is enhanced to provide a powerful antibacterial agent exceeding the activity of silver. ICP-MS elemental analysis and UV-spectroscopy indicated that the enhanced bactericidal effects of the synthesized composite, CH@Cu, are associated with the sustained release of both copper ions and CH, giving rise to synergistically enhanced activity.